Barriers and facilitators of child and guardian attendance in task-shifted mental health services in schools in western Kenya. (2020) - Meza, Rosemary D.; Kiche, Sharon; Soi, Caroline; Khairuzzaman, Alya N.; Nales, Cristian J. Rivera; Whetten, Kathryn; Wasonga, Augustine I.; Amanya, Cyrilla; Dorsey, Shannon
Abstract: Background: Globally, nearly 140 million children have experienced the death of one or both parents, and as a result many experience higher rates of mental health problems. Trauma-focused cognitive behavioral therapy (TF-CBT) delivered by lay counselors has been shown to improve mental health outcomes for children experiencing traumatic grief due to parental loss; however, challenges with treatment attendance limit the public health impact of mental health services. This study used qualitative methods to assess barriers and facilitators of child and guardian attendance of school-based lay counselor delivered TF-CBT. Methods: Semi-structured interviews were conducted with 36 lay counselors (18 teachers; 18 community health volunteers) who delivered TF-CBT to explore their perceptions of barriers of facilitators of child and guardian attendance of group-based sessions delivered in schools. Results: Counselors identified attendance barriers and facilitators related to the delivery setting, resources, participant characteristics, intervention characteristics and counselor behaviors. The findings revealed a greater number of facilitators than barriers. Common facilitators included participant and counselor resources, counselor commitment behaviors and communication efforts to encourage attendance. Barriers were less frequently endorsed, with participant resources, child or guardian illness and communication challenges most commonly mentioned. Conclusions: Attention to barriers and facilitators of attendance in the context in which mental health interventions are delivered allows for identification of ways to improve attendance and treatment engagement and achieve the potential promise of providing accessible mental health services.